Aerodynamic performance of flying discs. Issue 2 (5th March 2018) - Kamaruddin, Noorfazreena; Potts, Jonathan; Crowther, William
Abstract : Purpose: The purpose of this paper is to examine geometrical design influence of various types of flying discs on their flight performance from the aerodynamics perspective. Design/methodology/approach: The lift, drag and moment coefficients of the discs were measured experimentally using a wind tunnel. Three types of golf discs and four sets of simpler parametric discs were studied to analyze and isolate the effect of design factors on these aerodynamic characteristics. Full six degree-of-freedom simulations of the discs were performed to visualize their flight trajectories and attitudes. These simulations, combined with the experimental data, provide details on the well-known "S-shaped" ground-path traced by a flying disc. Findings: This paper reveals two key parameters to evaluate the flight performance of a disc: its coefficient of lift-to-drag ratio (CL/CD) and, more importantly, its coefficient of pitching moment (CM). The latter influences the tendency of the disc to yaw from its intended path, and the former influences its throwing distance. Practical implications: The work suggests that to optimize the flight performance of a disc, the magnitudes and gradient of its CM should be minimized and its trim-point shifted from origin, while its CL/CD should be maximized with a flatter peak. Originality/value: In this paper, the design parameters and the aerodynamic characteristics of various types of flying discs are analysed, compared and discussed in depth. Recommendations of design improvements to enhance the performance of any flying disc are offered as well.